Application of temporary adherence to improve the manufacturing of 3D thin silicon wafers. (June 2019) - Abadie, K.; Montméat, P.; Enot, T.; Fournel, F.; Wimplinger, M.
Abstract: The presented work concerns the manufacturing of very thin silicon wafers for a 3D Integrated Circuit industrial purpose. One of the key parameters of the 3D integration is the adherence of the bonded structure which involves silicon wafers and a polymer adhesive as an intermediate layer. The scope of the paper is to determine the suitable adherence of the stack for a successful manufacturing onto industrial tools. For this purpose the dismounting capacity of the fully automated equipment EVG ® 850DB depending on the adherence energy is studied. Direct and polymer bonded silicon pairs are prepared. Their energies of adherence cover a large range of energy: from 0.3 to 14 J/m 2 . The automatic mechanical dismounting process is successful when the stack adherence is 1.2 J/m 2 or lower. This value does not depend on the bonded structure type: direct bonded pairs or thinned polymer bonded pairs exhibit the same behavior regarding the dismounting capacity. And we demonstrate that the industrial manufacturing of 70 μm thin silicon wafers is possible if the adherence is 0.4 J/m 2 to 1.2 J/m 2 .